Kelayakan Media Interaktif Berbasis Quizizz Pada Materi Sistem Reproduksi - Ningsih, Kurnia; Afandi, Afandi; Yuniarti, Anisyah; Nurfitriani, Dina (Jurnal Biotek, 2023)
Technology is used in educational materials to aid in students' comprehension of the subject matter and to prevent boredom during the learning process. This research examined the viability of interactive Quizizz-based media for class XI subjects on the reproductive system. This research and development (R&D) was using the ADDIE development model. The ADDIE development model is restricted and includes only analysis, design, and development stages. The research was conducted from February to July 2022. The Quizizz interactive media was validated by three high school biology teachers and two lecturers, and this validation served as the study's instrument. Aiken's V analysis showed an average of 0.95, confirming validity, while the ICC reliability analysis indicated 0.795, falling within the good category. These findings support the use of Quizizz interactive media as a learning tool for reproductive system material. Future studies should focus on different biological materials.